Religion for Naturalists and the Meaning of Belief - Deng, Natalja (European journal for philosophy of religion, 2019)
This article relates the philosophical discussion on naturalistic religious practice to Tim Crane's The Meaning of Belief: Religion from an Atheist's Point of View, in which he claims that atheists can derive no genuine solace from religion. I argue that Crane's claim is a little too strong. There is a sense in which atheists can derive solace from religion and that fact is worth acknowledging (whether or not this counts as genuine' solace).